Improvement Options and Directions for Crisis Management Exercises Organised by Local Governmental Administration on the Example of Podkarpackie Voivodship — Theoretical Assumptions - Bernard Wiśniewski; Andrzej Czupryński; Jan Ziobro; Karol Kujawa (Safety & Fire Technology)
Aim: The objective of the presented analysis is to offer theoretical assumptions for the research work of the team appointed for the purposes of the Voivodship Crisis Management Team exercises organised by the Voivode of Podkarpackie. The authors present the basis for developing the methodology of the project aiming at defining the options and methods for improving the exercises organised by local governmental administration. Introduction: The analyses conducted by the above-mentioned team aimed at finding sources of knowledge and information related to the organisation of exercises by local governmental administration and determination of the practical usability of the related scientific theories. The works conducted involved such specific problems as: definition of the essentials of the organisation of crisis management pratice activities by local governmental administration, identification of organisation improvement needs related to crisis management by local governmental administration and definition of the conditions and perspectives for the improvement of the organisation of the subject exercises. The adopted assumptions indicated that the options of improvement of the organisation of exercises by the local governmental administration of Podkarpackie Voivodship should be sought in the emerging new organisational solutions and access to the preparation and completion analytics and efficiency assessment tools. Methodology: The authors focused on the review of the methodological assumptions of exercises and the applicable regulations and documents used in the public administration office serving the Voivode and local government bodies of Podkarpackie Voivodship Conclusions: The above-mentioned review confirmed the belief in the importance of exercises for the crisis operations improvement process. It is crucial for the preparation of the local communities for emergencies. Above all, it enables the practical application of crisis management plans, which enables identifying deficiencies and areas to improve. Those operations may be improved by preparing a scientific approach to the organisation and assessment of exercises and selection of appropriate legal and scientific bases. The next stage in the works of the authors team will consist in the analysis of local exercises and drawing comprehensive conclusions. Keywords: security, defence, crisis management, exercises, research, administration